Bronchoscopic Lung Volume Reduction as Therapy in Chronic Obstructive Pulmonary Disease (COPD) Patients with Emphysema - Rullian, Harry Pasca; Deddy Herman; Dessy Mizarti (HM Publisher, 2024)
BLVR is a combination of non-surgical techniques for lung volume reduction performed via bronchoscopy as an alternative to LVRS in emphysema patients. The techniques most often used in BLVR are bronchial valves (EBV/IBV), coils (lung coil), and thermal vapor (BTVA), while the BioLVR and ABS techniques have begun to be abandoned. BLVR is generally beneficial in improving lung function, exercise capacity, and quality of life in patients with emphysema. There is a need to monitor post-procedure side effects and long-term follow-up to assess the effectiveness of the procedure and reduce complications.